Tax Administration and the Small Taxpayer - Shome, Parthasarathi (IMF Policy Discussion Papers; Policy Discussion Paper ;, 2004)
Small taxpayers should pay their appropriate revenue share while their compliance costs should be reduced. This assumes importance as restructuring in emerging markets has meant rapid growth in services through self-employed small entrepreneurs, who have good revenue potential. Administrative facilitators such as a single tax covering income tax, VAT, and social security tax, at a reduced rate, do not lower tax evasion. They increase vertical and horizontal inequity, and lead to adverse resource allocation. A strategy is needed, extending modernization achieved in large taxpayer units (LTUs) to small taxpayers, including rationalization of collection and reporting of revenue data for policy formulation.